Tetranectin, a potential novel diagnostic biomarker of heart failure, is expressed within the myocardium and associates with cardiac fibrosis - McDonald, Kenneth (Sci Rep, 2020)
Heart failure (HF) screening strategies require biomarkers to predict disease manifestation to aid HF surveillance and management programmes. The aim of this study was to validate a previous proteomics discovery programme that identified Tetranectin as a potential HF biomarker candidate based on expression level changes in asymptomatic patients at future risk for HF development. The initial study consisted of 132 patients, comprising of HF (n = 40), no-HF controls (n = 60), and cardiac surgery patients (n = 32). Serum samples were quantified for circulating levels of Tetranectin and a panel of circulating fibro-inflammatory markers. Cardiac tissue served as a resource to investigate the relationship between cardiac Tetranectin levels and fibrosis and inflammation within the myocardium. An independent cohort of 224 patients with or without HF was used to validate serum Tetranectin levels. Results show that circulating Tetranectin levels are significantly reduced in HF patients (p < 0.0001), and are associated with HF more closely than B-type natriuretic peptide (AUC = 0.97 versus 0.84, p = 0.011). Serum Tetranectin negatively correlated with circulating fibrosis markers, whereas cardiac tissue Tetranectin correlated positively with fibrotic genes and protein within the myocardium. In conclusion, we report for the first time that Tetranectin is a promising HF biomarker candidate linked with fibrotic processes within the myocardium.